Effect of Seed Size and Weight on Germination Pattern and Seedling Development of some Multipurpose Tree Species of Garhwal Himalaya - Negi, A. K.; Todaria, N. P. (Indian Forester, 1997)
The influence of seed size and weight on seed germination behaviour and development of Acer oblongum, Kydia calyciana, Terminalia tomeutosa, T. belerica, T. chebula have been investigated. Heavy and large seeds of T. belerica and A. oblongum performed better in term of germination pattern while T. belerica and T. tomentosa gave better results in term of seedling development after 3 month and 6 month respectively.